Adsorption of Remazol Brilliant Violet 5R (RBV-5R) and Remazol Brilliant Blue R (RBBR) from Aqueous Solution by Using Agriculture Waste - Hong Jian Lai (Tecno Scientifica Publishing, 2021)
The ability of agricultural waste materials to remove synthetic dyes such as Remazol Brilliant Violet 5R (RBV-5R) and Remazol Brilliant Blue R (RBBR) from aqueous solutions was investigated. Dyes are a major source of water contamination that not only cause significant damage to water bodies but also have a negative effect on human health due to their high toxicity and carcinogenic nature. Agricultural wastes are renewable adsorbents because they are readily available and inexpensive, and they can also be used instead of conventional activated carbon. As a result, the removal of RBV-5R and RBBR from dye solutions by adsorption onto treated adsorbent was investigated in this review. The two best adsorbents out of ten were selected via a screening process with RBBR as the test dye. The key adsorbents in this analysis were coconut shells and mango seeds, which had the highest removal rate as compared to others. The experiment was continued with the chosen adsorbent to see how different initial dye concentrations, adsorbent dosage, contact time, pH, and particle size affected dye adsorption. The results show that different parameters have different effects on the removal rate and adsorption potential of the adsorbent. The adsorption of dye from aqueous solution onto adsorbent was investigated using Fourier transform infrared spectroscopy (FTIR) to investigate the functional groups of the adsorbent before and after the adsorption operation, and it was discovered that the functional group affected the effectiveness or removal rate as well as the adsorption capability of adsorbents. According to the findings, 5 gram mango seeds can extract 85.54 percent of RBV-5R with adsorption power of 1.26 mg/g. For 21 hours, coconut shells removed 74.39 percent of RBBR with an adsorption capacity of 8.01 mg/g. The findings indicated that these agricultural wastes could be useful as an alternative adsorbent for removing dye from aqueous solutions.